Socio-Historical Media Tourism Promotion Study during the Dutch East Indies Period of 1930 - 1940 (Paramita: Historical Studies Journal, 2020)
This study discusses the media of tourism promotion in the Dutch East Indies period, in the form of lithographic print art images. The purpose of this research is to determine the meaning of visual language in the promotional media images. Promotional objects in question are pictures of lodging, photos of exotic cultural and natural products of the colonies insulinde printed between 1930 and 1940. With socio-historical methods consisting of social and historical studies, data obtained from literature studies, literature studies, and field observations will be analyzed using Teun A. van Dijkâ€™s critical discourse approach. Furthermore, the results of the study will be interpreted descriptive qualitatively and presented with a historiographic approach. The findings of this study are there had been a process of Westernization in visual culture in the colonial period. The conclusion of this research is the portrayal of media promotion tourism during the Dutch East Indies of 1930-1940, which has given birth to traces of art deco style lithographic print as an effort of modernization in supporting modernity and developing a modernistic Dutch colonialist tourism aimed at European travelers.Â Penelitian ini membahas tentang media promosi wisata di masa kolonial Belanda, berupa gambar seni cetak litografi. Tujuan penelitian untuk mengetahui makna bahasa rupa yang ada dalam gambar media promosi tersebut. Objek promosi yang dimaksud adalah gambar penginapan, gambar hasil budaya dan alam eksotik pedalaman tanah jajahan insulinde yang dicetak antara tahun 1930 hingga 1940. Dengan metode sosio historis yang terdiri dari kajian sosial dan sejarah, data yang diperoleh dari studi literatur, kajian pustaka dan observasi lapangan akan dianalisis dengan pendekatan wacana kritis Teun A. van Dijk. Selanjutnya berdasarkan data yang ada, hasil penelitian akan diintepretasikan secara deskriptif kualitatif dan dipaparkan dengan pendekatan historiografi. Hasil temuan dari penelitian ini adalah bahwa telah terjadi proses pembaratan dalam budaya visual di masa kolonial. Adapun kesimpulan penelitian ini yaitu penggambaran media promosi wisata masa Hindia Belanda 1930 - 1940, telah melahirkan jejak seni cetak litografi bergaya art deco sebagai upaya modernisasi dalam mendukung modernitas dan memajukan pariwisata kolonialis Belanda yang modernistik di Hindia Belanda yang ditujukan bagi pelancong orang-orang Eropa.Â